Postmillenial Netizens' Reception of Da'wah Messages on Social Media - Muhammad Qadaruddin; Wahyuddin Bakri (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2022)
Content of proselytizing at receptions differently. Da'wah content on social media is a negotiation process. Da'wah's content shows the potential position of postmillennial netizens as active meaning. They are free to choose proselytizing content. This research uses a qualitative method with an interpretive approach. The data were analyzed to find the postmillennial netizens' reception pattern. This research was conducted at State Islamic Religious universities in South Sulawesi Province. There are three groups in the reception of proselytizing content on social media. Firstly, netizen postmillennial oppositional position. In this group, postmillennial netizens are inconsistent in particular groups but watch a variety of messages and preachers. In this group, netizens examine religious concepts from multiple sources. The second negotiated position of this group is postmillenial netizens fanatical on certain mubaligh but still, put tabayyun on certain mubaligh. A third hegemonic position is a militant group without putting forward the principle of tabayyun. However, in this study, social media is a medium that offers various types of preaching and different proselytizing messages. So, some netizens experience the hybridization of proselytizing messages. But some netizens do not experience hybridization of religious understanding because they only watch certain mubaligh.